Enzymatic suppression activity of Alpinia galanga extract against polyphagous lepidopteran pest Spodoptera litura (Fabricius). (14th December 2021) - Datta, Rahul; Kaur, Amandeep; Saraf, Isha; Singh, Inder Pal; Kaur, Sanehdeep
Abstract: Plants produce a wide variety of metabolites in order to defend themselves against herbivore insects. To cope with the adverse effects of secondary metabolites, insects have also developed a variety of mechanisms including production of digestive and detoxifying enzymes. These enzymes provide benefit to insects by converting complex molecules into simpler form as well as help in detoxification of deleterious plant metabolites. The current study evaluated the effect of ethyl acetate extract of Alpinia galanga on digestive and detoxifying enzymes of Spodoptera litura (Fab). The larvae were fed on diet treated with different concentrations of the extract viz. 500, 1000, 1500, 2000 and 2500 ppm and the enzyme activity was observed after 48 and 96 hrs of feeding. The results revealed that the activity level of digestive enzymes viz. α-amylase, α and β-glucosidases, α and β-galactosidases and lipases decreased due to consumption of treated diet by the larvae. Similarly detoxifying enzymes viz. phosphatases and glutathione- S -transferases were also found to be suppressed. In conclusion, ethyl acetate extract of A. galanga exhibited enzyme inhibitory activity against S. litura .